The epitopes of influenza nucleoprotein recognized by cytotoxic T lymphocytes can be defined with short synthetic peptides. - Townsend, A; Rothbard, J; Gotch, F; Bahadur, G; Wraith, D; Mcmichael, A (1986)
A proportion of cytotoxic T lymphocytes (CTL) responding to infection by influenza recognize target cells that express the viral nucleoprotein. Recent work showed that CTL can recognize short overlapping regions of large nucleoprotein fragments expressed in transfected L cells. This led to the suggestion that CTL recognize segmental epitopes of denatured or degraded proteins in a similar way to helper T cells. One corollary of this idea is that CTL should recognize appropriate short peptides on the target cell surface. We demonstrate that the epitopes of nucleoprotein recognized by CTL in association with class I molecules of the major histocompatibility complex in both mouse and man can be defined with short synthetic peptides derived from the nucleoprotein sequence.